Challenges for High School Students during the Pandemic to Increase Self-efficacy: A Literature Review Study - Majid, Norma (Academia Edu Cendekia Indonesia (AEDUCIA), 2022)
The latest facts on the ground, the Covid-19 pandemic crisis has caused damage in various sectors. In the world of education there are already 258 million children and adolescents who have dropped out of school. Boredom, not understanding lessons, stress due to academic load, inadequate internet quota, and lack of facilities and infrastructure to support the distance learning process. This study aims to discuss the challenges of student self-efficacy in maintaining learning motivation and academic achievement during online learning. This research method uses literature review by examining various relevant reference sources related to self-efficacy based on the last five-ten years, especially the last two years during the Covid-19 pandemic. The results of the study revealed that there were still advantages and disadvantages found in distance learning during the pandemic on students' self-efficacy. The results of the study revealed that the strengths and weaknesses can be used as evaluation material to improve the quality of the teaching and learning process to improve students' self-efficacy. It can be concluded that interventions to deal with students' self-efficacy challenges during a pandemic are not only an evaluation to improve the quality of education but also have a positive impact on the development of students' self-efficacy in the future.